High yield of monoacylglycerols production through low‐temperature chemical and enzymatic glycerolysis. Issue 6 (15th April 2013) - Zhong, Nanjing; Li, Lin; Xu, Xuebing; Cheong, Ling‐Zhi; Xu, Zhenbo; Li, Bing
Abstract The present study aimed to produce MAG through low‐temperature chemical glycerolysis. Over 80% MAG yield with 97% TAG conversion was obtained within short reaction times at temperature of 35–55°C, when tert‐butanol (TB) or tert‐pentanol (TP) was used as reaction medium and sodium hydroxide (NaOH) as catalyst. TB gave a faster reaction rate than TP. Catalysts were important for the low‐temperature chemical glycerolysis reaction. Of the eight common base catalysts evaluated, only NaOH and potassium hydroxide (KOH) were effective, and NaOH was better than KOH. Reaction parameters were studied and optimized. The optimum conditions were TB dosage 3:1 (TB to oil in weight ratio), NaOH concentration 0.45 wt% based on oil, molar ratio of glycerol to oil 5:1. Under these conditions, similar MAG yield and TAG conversion was also observed by Novozym 435 catalyzed glycerolysis, however, a 4 h reaction was required. Practical applications: The process of NaOH catalyzed chemical glycerolysis for MAG production in TB solvent system described in this study provides several advantages including short reaction time and high product yield, which is potential for industrial considerations.